Spatial distribution and abundance of the by‐catch coastal elasmobranch Raja undulata: Managing a fishery after moratorium. (21st March 2020) - Figueiredo, Ivone; Maia, Catarina; Carvalho, Lucília
Abstract: The undulate ray Raja undulata Lacepède is a coastal species common along the north‐eastern Atlantic Ocean and Mediterranean Sea and is highly accessible to coastal fisheries. Between 2009 and 2015, the species was under a European Union (EU) fisheries moratorium that hampered the collection of data to assess its stock status in Portuguese waters. After that period, a small experimental EU fishing quota was set for Portugal enabling collection of fishery data under a fishermen self‐sampling scenario. Based on the data collected, R. undulata abundance was estimated along the Portuguese continental coast through the application of a N‐mixture model and incorporating environmental factors. The results support the species coastal and patchy nature across the study area with higher abundances estimated in areas associated with shallow sandy bottoms as the Southwest region. The present work constitutes an important step for the management of this fishery resource, in particular concerns about its abundance trends over time and its spatial distribution and habitat requirements.